In vitro motility of a population of clinical Burkholderia pseudomallei isolates. - Boonbumrung, K; Wuthiekanun, V; Rengpipat, S; Day, N; Peacock, S (2006)
Melioidosis, a serious infection caused by Burkholderia pseudomallei, is a leading cause of community-acquired sepsis in Northeast Thailand, and the commonest cause of death from community-acquired pneumonia in the Top End of Northern Australia. The causative organism is a Gram-negative, motile bacillus that is a facultative intracellular pathogen. B. pseudomallei flagella have been proposed as a possible vaccine candidate and putative virulence determinant. Flagella expression was highly conserved for 205 clinical B. pseudomallei isolates, as defined by in vitro swim and swarm motility assays. No association was found between motility and clinical factors including bacteremia and death.